The law of compulsory purchase - Honey, Richard; Pereira, James; Daly, Caroline; Clutten, Rebecca (London [England] : Bloomsbury Professional, 2022)
"Being spread across several statutes of varying antiquity and many judicial decisions, the law relating to compulsory purchase and compensation can appear daunting. This authoritative book is your single accessible volume to this complex and wide-ranging area of the law by setting out the practice, procedure, policy and valuation of a compulsory purchase. It provides a summarised statement of the law, complete with footnotes to enable you to access further information. It contains full cross-referencing to the relevant cases, statutory provision and policy circulars. It also includes a full explanation of the scope of powers to acquire land compulsorily and the exercise of the powers and principles of compensation. Find the answers you need quickly and easily. The practical structure, style and indexing ensures that the relevant statutory provisions and cases to the matters in issue are easy to find. It both simplifies what can be simplified and explains with clarity the difficult areas. This book should be on the desk of every practitioner who has to advise upon this branch of law and every advocate who has to present a case in which it arises."--
Introduction; -- Chapter 1: Powers of compulsory purchase; -- Chapter 2: Compulsory purchase orders and procedure; -- Chapter 3: Implementation of compulsory purchase; -- Chapter 4: Compensation for compulsory purchase; -- Chapter 5: Compensation where no land taken; -- Chapter 5: Compensation for decisions, controls and works; -- Chapter 6: Determination and recovery of compensation.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Eminent domain -- Great Britain; Compensation (Law) -- Great Britain; Eminent domain -- Wales; Compensation (Law) -- Wales; Electronic books